Leading your team through change technique and strategies needed to alter the behaviour of your team - Newton, Richard 1964- (Pearson, 2014)
If you need to be in the know in no time at all, Business Express will get you from beginner to brilliant in the blink of an eye. This fast, focused and carefully crafted eBook will help you pick up all the essential knowledge you need about the skills that matter most at work, all in the shortest possible time. Learn just when you need to or well in advance; read it at your desk or on the move; dip in and out or start from scratch - it's all up to you. But however you use it, you'll quickly feel more confident, competent and better equipped to make things happen and keep moving ahead. Save time -#x90; it's quick and easy to read Get smart -#x90; just the essential knowledge you need Feel good - watch your confidence grow Business Express -#x90; know how in no time!
Online resource; title from t.p. (Safari, viewed September 29, 2014)
Keywords: Organizational change; Leadership; Teams in the workplace; Organizational Innovation; Changement organisationnel; Équipes de travail